STUDIES ON IN VITRO EVALUATION OF ANTFUNGALACTIVITIES OF STERCULIA FOETIDA L. BARK - AKHTARI KHATOON; ASHIRBAD MOHAPATRA; KUNJA BIHARI SATAPATHY (International Journal of Pharma and Bio Sciences, 2016)
The present investigation was attempted in order to evaluate the antifungal potential of successively extracted n-hexane and methanolic extracts of Sterculia foetida L. bark. The fungi-toxic efficacy of the extracts was tested against both yeast like fungi [Candida albicans (MTCC-3017), Candida krusei, Candida tropicalis, Cryptococcus marinus (MTCC-1029)] as well as mycelial like fungi such as Aspergillus niger (MTCC-9933) and Rhizopus oryzae employing well diffusion and poison food method respectively. The study revealed that n-hexane extract in high inhibition against Candida krusei, whereas Candida albicans and Candida tropicalis showed no response and Cryptococcus marinus responded moderately. The methanolic extract showed high inhibition against Candida krusei, whereas Candida albicans and Candida tropicalis showed no response and moderate effect against Cryptococcus marinus. The n-hexane and methanolic extracts of this plant showed better zone of inhibition against Aspergillus niger than Rhizopus oryzae. Fluconazole and Clotrimazole were taken as reference antifungal.